Atypical rapid audio‐visual temporal recalibration in autism spectrum disorders. Issue 1 (9th May 2016) - Noel, Jean‐Paul; De Niear, Matthew A.; Stevenson, Ryan; Alais, David; Wallace, Mark T.
Abstract : Changes in sensory and multisensory function are increasingly recognized as a common phenotypic characteristic of Autism Spectrum Disorders (ASD). Furthermore, much recent evidence suggests that sensory disturbances likely play an important role in contributing to social communication weaknesses—one of the core diagnostic features of ASD. An established sensory disturbance observed in ASD is reduced audiovisual temporal acuity. In the current study, we substantially extend these explorations of multisensory temporal function within the framework that an inability to rapidly recalibrate to changes in audiovisual temporal relations may play an important and under‐recognized role in ASD. In the paradigm, we present ASD and typically developing (TD) children and adolescents with asynchronous audiovisual stimuli of varying levels of complexity and ask them to perform a simultaneity judgment (SJ). In the critical analysis, we test audiovisual temporal processing on trial t as a condition of trial t  − 1. The results demonstrate that individuals with ASD fail to rapidly recalibrate to audiovisual asynchronies in an equivalent manner to their TD counterparts for simple and non‐linguistic stimuli (i.e., flashes and beeps, hand‐held tools), but exhibit comparable rapid recalibration for speech stimuli. These results are discussed in terms of prior work showing a speech‐specific deficit in audiovisual temporal function in ASD, and in light of current theories of autism focusing on sensory noise and stability of perceptual representations. Autism Res 2017, 10: 121–129 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.